PENDIDIKAN MORAL DALAM CERITA ANAK œSAMOSIR DAN œKELINCI YANG SERAKAH BAGI ANAK SEKOLAH DASAR - Harahap, Muharrina; Chairunnisa, Hera; Khairani, Ita; Anggreini, Heny (Universitas Negeri Medan, 2022)
The purpose of this study was to determine moral education in the children's stories